KOMPOSISI DAN MODIFIKASI NARASI PADA HOAKS BERULANG - Agus Ari Iswara (Linguistik Indonesia, 2021)
This research examined the comparison of hoax narratives that have been published and then recycled and re-published. The data source for this research was Turnbackhoax.id, an antidote to hoaxes media in Indonesia. Data were collected using online library methods and documentation techniques. Data triangulation was applied on the Turnbackhoax.id page so that the data used had been verified as a hoax. Data analysis used the side-by-side comparison method in the Plagiarism Checker application. The analysis was assisted by triangulation with theories. Data and analysis were presented descriptively. Based on the side-by-side comparison method, the narratives on the old hoaxes that were republished varied, performed a slight modification, performed many modifications, modifications with additional narratives, and eliminated narratives. The composition or a narrative framework of hoaxes also varied. There were the head; salutation; dateline; lead; body; and closing which was followed by a complimentary close and the element of ‘So What’. There were also hoax narratives that did not have complete elements of the head, salutation, dateline, lead, body, and closing. Information in old and recycled hoax narratives did not have a complete 5W+1H (What, Who, When, Where, Why, How) element and the information was unclear and fictitious. Hoaxes generally contain ‘So What’ elements with imperative narratives with persuasive or provocative diction.